Investigating factors influencing quality-of-life effects of home care services in Austria, England and Finland: A comparative analysis. (May 2021) - Trukeschitz, Birgit; Hajji, Assma; Kieninger, Judith; Malley, Juliette; Linnosmaa, Ismo; Forder, Julien
European countries have developed a range of long-term care (LTC) policy responses to support the increasing share of older people. However, little is known about the effectiveness of LTC services and benefits, particularly their impact on older peoples' quality of life (QoL). This paper investigates the role of personal, care service and environmental characteristics on the effects of home care services on QoL across England, Finland and Austria. We used data from surveys conducted in England, Finland and Austria. In total, 811 older adults were included in the analysis. OLS regression including main effects and country-specific interactions was used to explore variation in gains in long-term care service-related quality-of-life (LTC-QoL). Explanatory variables were derived from the production of welfare framework and comprised home care service user socio-demographics, needs indicators, social support and environmental variables and characteristics of home care service provision. In all three countries, LTC-QoL gains increased with needs, indicating that home care services perform well, with additional gains declining the higher the needs. Also, better process quality contributed to LTC-QoL improvements in all three countries. In addition, the availability of informal care, social contact, financial household situation and living alone, were associated with changes in LTC-QoL only in one or two of the countries. Home care services increased service users' QoL in all three European countries. The increase in QoL, however, varied across the countries. The results also provide insights into the benefits and limits of home care service provision and areas for future improvements. JEL: I31, I38, J14